Rain Water Harvesting Sebagai Alternatif Pemanfaatan Sumber Daya Air Di Dusun Mari Bangun dan Mekar Baru - Wahyudi, Moh Ikhwan; Fina Rafika Haque; Aulia Ade Putri; Mohammad Ibnu Praditya; Dhina Syalsabillah Nispayani; Rendy Agusti; Mustafa Wadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
Water is anything that is above or below ground level. Water is a fundamental thing that humans need for their daily survival, so the fulfillment of clean water for the community is very important. Naturally, water can be found in three main sources, namely groundwater, surface water, and rainwater. Rainwater is a source of water that is easy to obtain and can be utilized by everyone. According to BMKG, rainfall in Indonesia in a year reaches 1,562.6 mm3. Mari Bangun -Mekar Baru Hamlets have problems in fulfilling clean water for daily needs. This community service activity aims to create a rain water harvesting system so that people have a more affordable alternative in meeting their daily clean water needs. Rain water harvesting is a rainwater collection technique using a large surface that will be forwarded into a storage tank so that it can be utilized for daily needs. The results obtained from this manufacture are that rainwater can be collected in the reservoir well and dry leaves or wood can be avoided from being mixed into the water reservoir.